Weed science education and research: the agronomy learning farm and mesotrione and sulfonylurea herbicide interactions - Schuster, Christopher Louis (Kansas State University, 2007)
This dissertation has two complementary components: educational, in a survey of students in Weed Science and their perception of the Kansas State University Agronomy Learning farm, and research, regarding interactions between mesotrione and sulfonylurea herbicides. The Learning Farm serves as a resource where undergraduate students at KSU can develop agronomic skills through hands-on field site experiences and investigations. Students’ perceptions of experiential learning activities in the development of problem-solving and critical thinking skills were studied as a result of the Learning Farm. Activities included: undergraduate students in Weed Science (AGRON 330) developing a weed management recommendation, and Undergraduate Research Assistants (URAs) conducting weed science research projects at the Learning Farm. Students stated that experiential learning activities increased their critical thinking skills, required effective time management, and presented concepts that could be used in other situations. Pre- and post-project evaluation questionnaires showed that URAs had an increased interest in agronomy, weed science, and research following the completion of their project. For the research project, field and greenhouse studies were conducted from 2003 to 2006 to evaluate the efficacy of various sulfonylurea herbicides when applied with mesotrione or mesotrione + atrazine. Research demonstrated that the addition of mesotrione to sulfonylurea herbicides decreased efficacy of sulfonylurea herbicides on green foxtail, yellow foxtail, and shattercane. The addition of atrazine to the tank mix, or increased mesotrione rates, resulted in additional decrease in sulfonylurea herbicide efficacy on shattercane and foxtail species. Additional studies were performed to determine if absorption, translocation, or metabolism was the basis for the reduction in sulfonylurea herbicide efficacy when mixed with mesotrione or mesotrione + atrazine. Results indicated that the cause of antagonistic interaction between mesotrione and sulfonylurea herbicides in green and yellow foxtail was reduced absorption and translocation of the sulfonylurea herbicides. Producers who choose to apply mesotrione and sulfonylurea herbicides to corn should apply the herbicides sequentially to achieve maximum control of weedy grass species.
Keywords: Experiential-learning; Hands-on learning; Mesotrione; Antagonism; Agriculture, Agronomy (0285)